Дослідження сучасного стану функціонування системи оподаткування доходів фізичних осіб - Стригуль, Лариса Станіславівна; Зозуля, В. М. (НТУ "ХПІ", 2014)
У статті досліджено проблеми і недоліки функціонування системи нарахування та сплати податку на доходи фізичних осіб з рахуванням змін норм законодавства у сучасних умовах господарювання. Визначено фіскальне значення та роль податків у фінансуванні доходів бюджету, дослідженні чинники впливу на рівень і динаміку надходження податку на доходи фізичних осіб та забезпечення зростання життєвого рівня населення.

In article problems and lacks of functioning of system of charge and tax discharge on incomes of physical persons taking into account changes of rates of the legislation in modern conditions of managing are researched. The analysis of positions of the Tax code of Ukraine which regulate relations in the taxation of incomes of physical persons and an estimation of fiscal efficiency and socially-reguljativnoj role of the tax, and also the analysis of practice of the taxation of incomes of physical persons is performed, problems of the taxation of the tax and improvement of the mechanism of collecting NDFL in Ukraine are revealed. Fiscal value and role of taxes in financing of budget revenues is specified, factors of influence on level and dynamics of receipt of the tax to incomes of physical persons are researched. Factors of influence on level and dynamics of growth of a standard of life of the population are considered. The basic problems and features of the taxation of fund payments are researched at general system of the taxation. Recommendations about reduction of the sizes of advance fees on the basis of considerable reduction of taxation basis are offered.
Current state research functioning of system of the taxation of incomes of physical persons
Keywords: податкове законодавство; оподаткування; податкові надходження; податок на додану вартість; фінансування доходів бюджету; charge; taxation; expenses; value-added tax; incomes